2019
DOI: 10.3389/fpsyt.2019.00348
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Stressful Life Events and Sleep Quality: Rumination as a Mediator and Resilience as a Moderator

Abstract: Purpose: The aim of this study was to investigate the relationship between stressful life events and sleep quality and to probe the role of rumination and resilience in the relationship. Method: The Adolescent Self-Rating Life Events Checklist, Ruminative Responses Scale, Connor–Davidson Resilience Scale, and Pittsburgh Sleep Quality Index were used among 1,065 college students. Statistical Product and Service Solutions (SPSS) 20.0 and the SPSS macro Process, which were speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 55 publications
6
70
0
1
Order By: Relevance
“…For the first stage of the mediation process (i.e., stressors of COVID-19 → rumination), this study indicated that stressors of COVID-19 promoted the activation of rumination mechanisms. This finding is in line with prior literature on rumination and stress consequences, whereby rumination tendencies are partly mutable in response to stressful life events ( Li et al, 2019 , Liu and Wang, 2017 , Michl et al, 2013 ). Uncontrollable factors and stressors may create a dissonance between the ideal goal state and the reality state, leading to rumination ( Nolen-Hoeksema et al, 2008 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the first stage of the mediation process (i.e., stressors of COVID-19 → rumination), this study indicated that stressors of COVID-19 promoted the activation of rumination mechanisms. This finding is in line with prior literature on rumination and stress consequences, whereby rumination tendencies are partly mutable in response to stressful life events ( Li et al, 2019 , Liu and Wang, 2017 , Michl et al, 2013 ). Uncontrollable factors and stressors may create a dissonance between the ideal goal state and the reality state, leading to rumination ( Nolen-Hoeksema et al, 2008 ).…”
Section: Discussionsupporting
confidence: 92%
“…Participants rated each item on a four-point scale ranging from 1 (never) to 4 (always), with higher mean scores indicating higher levels of rumination. This scale has been used in the Chinese population (e.g., Chen et al, 2018 , Cui et al, 2017 , Li et al, 2019 , Wang et al, 2020b ​) and shown good reliability and validity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep is an important time for the recuperation and rejuvenation of the brain. Unfortunately, a substantial body literature showed stressful life events and outbreaks of infectious disease including COVID-19 can affect the sleep quality [21,[26][27][28][29], 84.69% of the participants in our study with the poor sleep quality demonstrate it again. Using the correlation analysis, we also found levels of anxiety symptoms are associate with sleep quality in COVID-19 patients admitted to shelter Fangcang hospital.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, it is found that sleep can also affect the glymphatic system to clear the big molecules in the brain [8], and it is reported that glymphatic system might induce depression in Alzheimer's disease [9]. Our previous studies also reported that sleep is an important time for the recuperation and rejuvenation of the brain [10]. In all, sleep can induce many kinds of neurological and psychological diseases, such as emotion disorders, substance use, low academic performance, and physical dysfunctions [11].…”
Section: Introductionmentioning
confidence: 93%